A DEVELOPMENT OF ENGLISH LEARNING COMPANION USING IMMERSIVE VIRTUAL REALITY APPLICATION - Amna, Shally; Permana, Randy; Christina, Dian (University of Kuningan, 2024)
This research developed an educational application based an immersive virtual reality application using a 360-degree camera and a software engine called Unity. The content in the application contains conversations with topics given in the English II course and listening comprehension skill exercises tailored to the needs of users, especially for Computer Science Faculty Students. Each exercise is given a score or value to monitor the improvement of students' listening skills before and after using the application. This research is part of Research and Development (R & D) research. In this study, a descriptive qualitative approach was used to explain the process, appearances, and results of application validation by six English lecturers. The result of this research was an immersive-based educational application with virtual reality technology for listening comprehension exercises using several features like text to speech, rotating 360-degree ability, and scoring system. This application achieved a validation value of 94 percent.The highest value of the validation results was the suitability of the application to the needs of students, while the lowest value of this application was the video display which still has to be improved again.